Characteristic of Travel Behavior from State Civil Apparatus at Bandar Lampung Goverment Office - Taha, Reski; Putra, Sasana; Sulistiyorini, Rahayu (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2019)
The office is a representation of the trip distribution. Travel behavior of the State Civil Apparatus (ASN) is one of the causes of transportation problems that occur. This condition is an idea to examine the activities of employees who have an influence on the productions and attraction zones that occur in Bandar Lampung Government Office.This research focuses on the characteristics and travel behavior of the State Civil Apparatus in Bandar Lampung Government Office with the existing land use. Data is collected by interview method. The analysis used is a descriptive crosstab analysis.From the results of the research, the percentage of the mode of travel used by the State Civil Apparatus is motorcycle, 59.17%; personal car 25.00%; and public transportation 15.83%. The most influential factor on the behavior of the State Civil Apparatus prefers to use personal vehicles compared to public vehicles, are time and distance traveled. The biggest production and attraction trip is in North Teluk Betung sub-district with the value of production is 48.79% and the attraction is 49.35%. Keywords: City Government Office, Mode of Travel, Trip Generation, Bandar Lampung